ANALISIS KINERJA PEGAWAI PADA DINAS KEBERSIHAN DAN PERTAMANAN KABUPATEN LAMPUNG SELATAN - Susilawati - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2016)
Work performance assessment is used to increase organization performance. A superiorofficial assessor in a functional is not only to give legality of assessment result from official assessor,but it is more function as motivator and evaluator how effective the official assessor assessed.Civil servant’s obligation that has clearly regulated and must be obeyed by every civilservant is the form of discipline that implanted in every civil servant which one of the goals is toimprove its performance.Nowadays Department of Cleanliness and Park South Lampung has supervision and goodincentive provision. It can be seen from many kinds of the existing rules and also motto organizationthat oriented in employees’ performance. From the analysis proves that the supervision andincentives have a positive influence to the employees’ performance.